cry1 genes from Bacillus thuringiensis: specificity determination and implications for primer design - Davolos, Camila C. [UNESP]; Guidelli-Thuler, Ana M. [UNESP]; de Abreu, Irlan L. [UNESP]; Sena, Janete A.D. [UNESP]; Lemos, Manoel V F (Springer, 2009)
Some pest management programs employ PCR to identify cry1 genes from Bacillus thuringiensis to predict bacterial toxicity towards different insect pests. However, due to changes on the mode of action of the Cry proteins, new primers had to be designed to detect the new genes. Therefore, an 'in-silico' study of genetic sequences from five cry1 subclasses was carried out and characterized by molecular tools. The design of new primers allows for more precise selection of B. thuringiensis isolates, helping to better direct the programs employing biological control.
Keywords: Cry proteins; cry1 subclasses; DNA sequencing; DNA homology; PCR